2013
DOI: 10.5402/2013/703230
|View full text |Cite
|
Sign up to set email alerts
|

Disease Control in Age Structure Population

Abstract: We combine the Leslie model and its derivatives with the classical compartmental SIRS models to build a model of transmission of infected diseases, in a population of hosts, whether opened or closed systems. We calculate the basic reproductive rate R 0 . Under certain conditions, when 0 < 1, there is a disease-free equilibrium that is locally asymptotically stable. In contrast, when 0 > 1, this equilibrium is unstable. en, through an example, we show how we can de�ne public health strategies to tackle an ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…In Table 2 we give the parameter values and the source from which the parameter values are taken. With these parameter values, we will numerically show the asymptotic stability of E 0 and E 1 based on the values of basic reproduction number in similar lines to [33].…”
Section: Parameters Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 2 we give the parameter values and the source from which the parameter values are taken. With these parameter values, we will numerically show the asymptotic stability of E 0 and E 1 based on the values of basic reproduction number in similar lines to [33].…”
Section: Parameters Valuesmentioning
confidence: 99%
“…Taking parameter values from Table 3, the system of Eqs. (2.1)-(2.6) was numerically [34] m 0.000182 [33] solved in math-lab. The solutions of the system (2.1)-(2.6) are depicted in Fig.…”
Section: Stability Of Infection Free Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…The classical approach consists of dividing the population into different groups, one for each age bracket under consideration, and establishing an age-dependent transmission rate. This transmission rate can be arranged in a matrix in which each element encodes the transmission probability between groups i and j (this matrix is also known as the Who Acquired Infection from Whom matrix [36,37]). It is also possible to separate the effect of the transmission itself in a common parameter and encode the number of contacts between each group in the matrix [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no enough epidemiological evidence to classify the age groups in transmission. Age structure modelling studies for diseases such as influenza and Dengue can be found in ( [16], [11]). Motivated by the above, in this study, we have proposed a non-linear age structured compartmental model in which the population is divided into two age groups.…”
Section: Introductionmentioning
confidence: 99%